MONITORING WATER QUALITY IN VEGETABLE HYDROPONICS USING ARDUINO MICROCONTROLLER - Windarsyah; Rudy Ansari; Ihdalhubbi Maulida; Ayu Ahadi Ningrum; Muhammad Alfiyani (Fakultas Teknik Universitas Lambung Mangkurat, 2022)
pH stands for the power of Hydrogen, which is an important factor in hydroponic systems. The hydrogen ion concentration determines the value of the acidity in the solution. If the pH value of the solution is below 7.0, then it is called acidic, and if the pH value is above 7.0, it is called alkaline. The pH value can change, so it is necessary to pay attention to the acidity of the water so that the roots absorb nutrients properly that farmers often find it difficult to take measurements. Mustard plants have a pH range of 5.5 – 6.5. Based on the pH range, it is necessary to have a tool to monitor the quality of the pH in mustard plants. This monitoring is carried out by creating a hydroponic nutrient water disposal system by combining agriculture and mechatronics. Mechatronics will control the nutrient distribution system so that it can be monitored with a smartphone via wireless connectivity such as the GSM module (800L. The water quality monitoring system works by using ultrasonic sensors, sensor probes and TDS sensors, as well as the GSM 800L module. monitoring of water quality in hydroponic mustard plants) using an Arduino microcontroller and detecting pH conditions and solute content. As for the disposal of nutrient water, using a water pump connected to the microcontroller via a relay. Based on the prototype carried out on June 26, 2021, the condition of water quality has decreased in nutritional quality with the first data (pH 6.31 solute 529 ppm) and the latest data (pH 9.09 and solute 662 ppm). When the water quality is below the nutritional standard, the water pump turns on to remove the nutrient water. The results of the prototype that has been carried out have succeeded in monitoring water quality hydroponics and can be used by farmers.